SIFAT PEMESINAN SEMBILAN JENIS KAYU DARI NUSA TENGGARA BARAT (Machining properties of nine wood species originated from West Nusa Tenggara) - Bakir Ginoga (Jurnal Penelitian Hasil Hutan, 1996)
The quality of machining properties of nine wood  species, i.e. gawil  (Mangifera altissima Blanco.); sana  (T erminalia  bellerica Roxb.); jinarti  (Symplocos brandisii  Ket   V.) ;  tunjang  gunung  (Neonauclea  schlecteri Merr.  et Perry); bayur  (Pterospermum  javanicum  Jungh.); klokos   (Eugenia   grandis    Wight.);  blahui   (Bischoffia  javanica   Bl.);   garu   (Dysoxylum  densiflorum  (Bl.)  Miq.);  and bangsal  (Engelhardtia spicata Lechen  ex B1.),  originated from natural forest in West Nusa Tenggara, has been investigated in air dried condition.The results revealed that the planing,  moulding and  sanding quality varies from  good (II) to very good(I); turning quality generally good (II); while boring quality varies from  very good(I)until verypoor classes (V).Keywords: Machining properties; wood species; natural forest; West Nusa Tenggara.